2018
DOI: 10.3390/educsci8040163
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Flipped-Classroom for Pre-Service Science Teachers

Abstract: The relatively new methodology, flipped-classroom, is one of blended learning instruction methodologies in which the traditional-classroom is inverted. This methodology asserts that students can participate and engage more successfully in their class and can attain better learning when their classroom is flipped. This work presents a two-year study to measure the effects of the flipped-classroom model on the performance, perceptions, and emotions for teacher training students in science education. Particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 26 publications
5
50
1
6
Order By: Relevance
“…Clearly, positive emotions are more frequent than negative ones (Figure 9). This is consistent with previously published work in the literature, for example Bujacz et al [39] obtained a correlation of positive emotions with creative activities, Suwal and Singh [40] found mainly positive emotions in the use of the Building Information Modelling (BIM) methodology using an online platform, Jeong et al proposed that active learning methodologies [12] and flipped classroom [13,32] cause positive emotions in students. On the contrary, Zamora et al found a plane emotional performance in a project-based learning activity developed using BIM in the university context [11].…”
Section: A) Descriptive Datasupporting
confidence: 90%
See 1 more Smart Citation
“…Clearly, positive emotions are more frequent than negative ones (Figure 9). This is consistent with previously published work in the literature, for example Bujacz et al [39] obtained a correlation of positive emotions with creative activities, Suwal and Singh [40] found mainly positive emotions in the use of the Building Information Modelling (BIM) methodology using an online platform, Jeong et al proposed that active learning methodologies [12] and flipped classroom [13,32] cause positive emotions in students. On the contrary, Zamora et al found a plane emotional performance in a project-based learning activity developed using BIM in the university context [11].…”
Section: A) Descriptive Datasupporting
confidence: 90%
“…Innovative methodologies are trending topic within the education spheres. Methodologies like flipped classroom, problem-based learning, design thinking or gamification are widely spread and many scholars are working on them, either at primary school level [7], high school [8] or higher education [5,[9][10][11][12][13][14]. Despite the relative novelty of such initiatives, obviously all of them respond to a very old question that is already stated out from a long time: How to engage more and better the students in the education process, making it a real excellent event?…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previously published works in the literature, for example, Bujacz et al [39], who obtained a correlation of positive emotions with creative activities, or Suwal and Singh [40], who found mainly positive emotions in the use of the building information modeling (BIM) methodology using an online platform. Similarly, Jeong et al proposed that active learning methodologies [41] and the flipped classroom cause positive emotions in students [23,30,42] and enhance science self-efficacy in preservice teachers [43]. By contrast, Zamora et al [8] found a plain emotional performance in a project-based learning activity developed using BIM in the university context.…”
Section: Descriptive Datamentioning
confidence: 99%
“…On the other hand, the student who used fewer emotional expressions is Blanca, a student who had initially a high online platform. Similarly, Jeong et al proposed that active learning methodologies [41] and the flipped classroom cause positive emotions in students [23,30,42] and enhance science self-efficacy in preservice teachers [43]. By contrast, Zamora et al [8] found a plain emotional performance in a project-based learning activity developed using BIM in the university context.…”
Section: Descriptive Datamentioning
confidence: 99%
“…Sci. 2019, 9, 116 2 of 13 applications can support and reinforce the concepts that students have previously been exposed to through lectures and/or textbooks, particularly in subjects in which the contents of mathematical and numerical calculations are applied to science education [10][11][12]. Still, only a few applications among a great variety of CAL systems have shown the ability to meaningfully connect and interact with science education.…”
Section: Computer-based Learning Environmentmentioning
confidence: 99%